Inflammatory therapeutic targets in coronary atherosclerosis—from molecular biology to clinical application - Linden, Fabian; Domschke, Gabriele; Erbel, Christian; Akhavanpoor, Mohammadreza; Katus, Hugo A.; Gleissner, Christian A. (Frontiers in Physiology, 2014)
Atherosclerosis is the leading cause of death worldwide. Over the past two decades, it has been clearly recognized that atherosclerosis is an inflammatory disease of the arterial wall. Accumulating data from animal experiments have supported this hypothesis, however, clinical applications making use of this knowledge remain scarce. In spite of optimal interventional and medical therapy, the risk for recurrent myocardial infarction remains by about 20% over three years after acute coronary syndromes, novel therapies to prevent atherogenesis or treat atherosclerosis are urgently needed. This review summarizes selected potential molecu-lar inflammatory targets that may be of clinical relevance. We also review recent and ongoing clinical trails that target inflammatory processes aiming at preventing adverse cardiovascular events. Overall, it seems surprising that translation of basic science into clinical practice has not been a great success. In conclusion, we propose to focus on specific efforts that promote translational science in order to improve outcome and prognosis of patients suffering from atherosclerosis.